'Necessary and sufficient' in biology is not necessarily necessary – confusions and erroneous conclusions resulting from misapplied logic in the field of biology, especially neuroscience. (3rd April 2018) - Yoshihara, Motojiro; Yoshihara, Motoyuki
Abstract: In this article, we describe an incorrect use of logic which involves the careless application of the 'necessary and sufficient' condition originally used in formal logic. This logical fallacy is causing frequent confusion in current biology, especially in neuroscience. In order to clarify this problem, we first dissect the structure of this incorrect logic (which we refer to as 'misapplied-N&S') to show how necessity and sufficiency in misapplied-N&S are not matching each other. Potential pitfalls of utilizing misapplied-N&S are exemplified by cases such as the discrediting of command neurons and other potentially key neurons, the distorting of truth in optogenetic studies, and the wrongful justification of studies with little meaning. In particular, the use of the word 'sufficient' in optogenetics tends to generate misunderstandings by opening up multiple interpretations. To avoid the confusion caused by the misleading logic, we now recommend using 'indispensable and inducing' instead of using 'necessary and sufficient.' However, we ultimately recommend fully articulating the limits of what our experiments suggest, not relying on such simple phrases. Only after this problem is fully understood and more rigorous language is demanded, can we finally interpret experimental results in an accurate way.